Proceedings of the 2019 International Conference on Organizational Innovation (ICOI 2019) 2019
DOI: 10.2991/icoi-19.2019.25
|View full text |Cite
|
Sign up to set email alerts
|

Green Human Resource Management, Green Organizational Culture, and Environmental Performance: An Empirical Study

Abstract: Ethical companies must balance their financial, social and environmental performance. The process of applying HR management objectives to environmental management is called Green Human Resource Management (GHRM). Research on GHRM and environmental performance in Indonesia is still limited in number, especially in South Sumatra. Based on the Environmental Quality Index reported by the Ministry of Environment and Forestry of the Republic of Indonesia, in 2016 South Sumatra was 16th national ranked, but slipped t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 14 publications
5
7
0
1
Order By: Relevance
“…H2. The findings supported Hadjri et al (2019) and Hardika et al (2019) studies which emphasized that green organizational culture is positively linked to environmental performance. The relationship of green organization culture on green innovation that is H3 was supported.…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…H2. The findings supported Hadjri et al (2019) and Hardika et al (2019) studies which emphasized that green organizational culture is positively linked to environmental performance. The relationship of green organization culture on green innovation that is H3 was supported.…”
Section: Resultssupporting
confidence: 84%
“…Wang (2019) found that green organizational culture strongly predicts environmental performance across 321 Taiwanese manufacturers from various industries. Hadjri et al (2019) and Hardika et al (2019) showed that green organizational culture is positively linked to environmental performance in Indonesian research. Manufacturing companies that want to improve their environmental performance should try to create a learning environment inside their "four walls" to quickly adjust to changing environmental factors (Afum et al, 2020).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The management should therefore emphasize the above practices. These findings support earlier findings by Hadjri, Perizade, and Farla (2019), which established a positive statistical relationship between Green Human Resource management and firm sustainability.…”
Section: Inferential Statisticssupporting
confidence: 92%
“…A comparative study was conducted by Hadjri, Perizade, and Farla (2019) on environmental management in manufacturing firms in Mexico. The study adopted a survey research design.…”
Section: Sustainabilitymentioning
confidence: 99%